Impact of in Utero Rat Exposure to 17Alpha-Ethinylestradiol or Genistein on Testicular Development and Germ Cell Gene Expression - Lecante, Laetitia L.; Gaye, Bintou; Delbes, Geraldine (Frontiers in Toxicology, 2022)
Although the decline in male fertility is believed to partially result from environmental exposures to xenoestrogens during critical developmental windows, the underlying mechanisms are still poorly understood. Experimental in utero exposures in rodents have demonstrated the negative impact of xenoestrogens on reproductive development, long-term adult reproductive function and offspring health. In addition, transcriptomic studies have demonstrated immediate effects on gene expression in fetal reproductive tissues, However, the immediate molecular effects on the developing germ cells have been poorly investigated. Here, we took advantage of a transgenic rat expressing the green fluorescent protein (GFP) specifically in germ cells allowing purification of perinatal GFP-positive germ cells. Timed-pregnant rats were exposed to ethinylestradiol (EE2, 2 µg/kg/d), genistein (GE, 10 mg/kg/d) or vehicle by gavage, from gestational days (GD) 13 to 19; testes were sampled at GD20 or post-natal (PND) 5 for histological analysis and sorting of GFP-positive cells. While EE2-exposed females gained less weight during treatment compared to controls, neither treatment affected the number of pups per litter, sex ratio, anogenital distance, or body and gonadal weights of the offspring. Although GE significantly decreased circulating testosterone at GD20, no change was observed in either testicular histology or germ cell and sertoli cell densities. Gene expression was assessed in GFP-positive cells using Affymetrix Rat Gene 2.0 ST microarrays. Analysis of differentially expressed genes (DEGs) (p<0.05; fold change 1.5) identified expression changes of 149 and 128 transcripts by EE2 and GE respectively at GD20, and 287 and 207 transcripts at PND5, revealing an increased effect after the end of treatment. Only about 1% of DEGs were common to both stages for each treatment. Functional analysis of coding DEG revealed an overrepresentation of olfactory transduction in all groups. In parallel, many non-coding RNAs were affected by both treatments, the most represented being small nucleolar and small nuclear RNAs. Our data suggest that despite no immediate toxic effects, fetal exposure to xenoestrogens can induce subtle immediate changes in germ cell gene expression. Moreover, the increased number of DEGs between GD20 and PND5 suggests an effect of early exposures with latent impact on later germ cell differentiation.